Descriptive and Vegetative Characterization of fifteen ecotypes of Snake Gourd (Trichosanthes cucumerina L.) in Nigeria - Osuagwu, Ann N.; Aguoru, C. U.; Omoigui, L. O.; Olasan, J. O. (Indonesian Journal of Agricultural Research, 2022)
The descriptive and vegetative characterization of fifteen ecotypes of Trichosanthes cucumerina L (snake gourd) in Nigeria was carried out. The field study was done in two locations Markurdi and Umudike to evaluate the descriptive and vegetative characters of fifteen ecotypes of T. cucumerina from Middle Belt of the country, the South-South, South Eastern part and South Western part of Nigeria. Randomized Completed Block Design was adopted for the experiment at the exploration farm of Michael Okpara University of Agriculture, Umudike and Federal University of Agriculture, Makurd at the same growing season. Descriptive and vegetative analysis was done using Minitab 16. The qualitative vegetative characteristic of snake gourd accessions vigour levels ranged from low, moderate and high. Leaf colour was from deep/pale/light green, stem colour was light, pale and deep green. The mean of the vegetative characters ranged from 2.7660-1575 ±0.48-99; cumulative variation percentage 7.65-64.75;. The germination percentage of all the accessions was significant (p<0.05). CRS – IKM (100+00), Osu – OSH – 2 (91.67±4.82).EKT – OYE was higher than Ben-MKDI (58.36±8.34). The plant height among the accessions was not significant, block was significant (P≤0.05). Leaf sizes (cm) of all the accessions were not significant (P>0.05), while main vine length (cm) at 5% probability was not significant and their treatment interaction was insignificant (P>0.05). The main vein length was highest in ABI-UKW with 636.0±164.0, followed by EKI-OYE 514.0±84.3 and least from RIV-ELE 275.7±26.4. The fruit colour at ninety days (90) of ten (10) accessions of snake guard was orange green or strip orange green and remaining accessions was milky green or light green. The fruit shape was long, thick and cylindrical. The seed colour was speckled russet.